2014
DOI: 10.5114/pg.2014.42503
|View full text |Cite
|
Sign up to set email alerts
|

IRS-2 G1057D polymorphism in Turkish patients with colorectal cancer

Abstract: IntroductionGene polymorphisms have a broad range of analysis, but are of particular use in molecular medicine due to their potential in revealing the genetic tendency in diseases such as cancer, heart attack etc. These studies basically depend on mutations that can be detected by proper techniques. The genes coding the insulin receptor substrate (IRS) proteins are among the most widely analysed polymorphisms in various cancer types, in which a G1057D mutation is seen.AimTo determine the risk of colon cancer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Among IRS2 polymorphisms, rs1805097G>A has been evaluated in six studies ( Table 5 ). Three of them have found that rs1805097G>A was not associated with CRC in Caucasian, Turkish and Iranian populations ( 36 , 41 , 45 ). The only significant result reported was in the study conducted by Slattery et al.…”
Section: Resultsmentioning
confidence: 99%
“…Among IRS2 polymorphisms, rs1805097G>A has been evaluated in six studies ( Table 5 ). Three of them have found that rs1805097G>A was not associated with CRC in Caucasian, Turkish and Iranian populations ( 36 , 41 , 45 ). The only significant result reported was in the study conducted by Slattery et al.…”
Section: Resultsmentioning
confidence: 99%
“…A study on Turkish subjects indicated that the variant allele of Asp1057 of IRS2 was associated with endometrial cancer, but they did not identify any influence on ovarian cancer (23,24). Another study in a Turkish population indicated that the IRS2 Gly1057Asp variant was not associated with colorectal cancer (25). On the other hand, a recent meta-analysis study indicated that the Asp1057 variant was associated with a decreased risk of colorectal cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…They only included 4 studies. To date, two studies [ 9 , 11 ] have been reported in recent years since the meta-analysis [ 20 ]. In analysis of all included studies, our meta-analysis found that rs1805097 polymorphism was associated with decreased CRC risk.…”
Section: Discussionmentioning
confidence: 99%